The land use, trade, and global food security impacts of an agroecological transition in the EU - Schiavo, Michele; Le Mouël, Chantal; Poux, Xavier; Aubert, Pierre-Marie (Frontiers in Sustainable Food Systems, 2023)
The need for an agroecological transition is regularly advocated by many actors and policymakers on the European scene, but many questions arise regarding the potential consequences that this transition may have on the rest of the world. Using a world biomass balance model, in this paper we show that a deep agroecological transition in the EU, if accompanied by a shift of EU food regimes towards more plant-based diets, is not detrimental to global food security. Without increasing its cropland areas, the EU can maintain the same level of exported calories as in a business-as-usual scenario while reducing its import needs. This result holds true also in an alternative scenario in which the other world regions adopt agroecological production methods and healthier diets. In contrast, an agricultural transition taking place in the EU without a change of EU food regimes, would drastically increase EU food dependence on global markets and contribute to the expansion of agricultural land in the rest of the world.